(untitled) (Research, Society and Development, 2023)
The changes brought about by Covid-19 significantly affected several areas and sectors, one of the most affected areas in terms of maintaining the process with adequate quality was the university environment. The Covid-19 pandemic has forced universities to move their infrastructure to fully distance and online teaching and learning environments in a short period of time. In this context, students were forced to adjust their established routines and concepts of teaching and learning. However, digital and remote learning measures are complex projects consisting of numerous conceptual and procedural steps that require planning and preparation time. The general objective of this research project was to identify which psychological impacts were caused during the pandemic period on the mental health of university students. The methodology used was bibliographic in nature. Analysis of research focusing on the mental health of university students during the Covid-19 pandemic indicated that different factors can affect the mental health of these individuals. As a result, it was observed that the factors that stood out the most were the following: fear of contagion, increased feeling of loneliness due to the need for social isolation, difficulties in adapting to the remote mode of teaching, excessive concern with personal, professional and social life. academic, increased anxiety and, finally, mourning the loss of loved ones.